Socioeconomic Determinants of Sodium Intake in Adult Populations of High-Income Countries: A Systematic Review and Meta-Analysis - de Mestral, Carlos (Am J Public Health, 2017)
Background. A poorer quality diet among individuals with low socioeconomic status (SES) may partly explain the higher burden of noncommunicable disease among disadvantaged populations. Because there is a link between sodium intake and noncommunicable diseases, we systematically reviewed the current evidence on the social patterning of sodium intake. Objectives. To conduct a systematic review and a meta-analysis of the evidence on the association between SES and sodium intake in healthy adult populations of high-income countries. Search Methods. We followed the PRISMA-Equity guidelines in conducting a literature search that ended June 3, 2016, via MEDLINE, Embase, and SciELO. We imposed no publication date limits. Selection Criteria. We considered only peer-reviewed articles meeting the following inclusion criteria: (1) reported a measure of sodium intake disaggregated by at least 1 measure of SES (education, income, occupation, or any other socioeconomic indicator); (2) were written in English, Spanish, Portuguese, French, or Italian; and (3) were conducted in a high-income country as defined by the World Bank (i.e., per capita national gross income was higher than $12 746). We also excluded articles that exclusively sampled low-SES individuals, pregnant women, children, adolescents, elderly participants, or diseased patients or that reported results from a trial or intervention. Data Collection and Analysis. As summary measures, we extracted (1) the direction (positive, negative, or neutral) and the magnitude of the association between each SES indicator and sodium intake, and (2) the estimated sodium intake according to SES level. When possible and if previously unreported, we calculated the magnitude of the relative difference in sodium intake between high- and low-SES groups for each article, applying this formula: ([value for high-SES group – value for low-SES group]/[value for high-SES group]) × 100. We considered an association significant if reported as such, and we set an arbitrary 10% relative difference as clinically relevant and significant. We conducted a meta-analysis of the relative difference in sodium intake between high- and low-SES groups. We included articles in the meta-analysis if they reported urine-based sodium estimates and provided the total participant numbers in the low- and high-SES groups, the estimated sodium intake means for each group (in mg/day or convertible units), and the SDs (or transformable measures). We chose a random-effects model to account for both within-study and between-study variance. Main Results. Fifty-one articles covering 19 high-income countries met our inclusion criteria. Of these, 22 used urine-based methods to assess sodium intake, and 30 used dietary surveys. These articles assessed 171 associations between SES and sodium intake. Among urine-based estimates, 67% were negative (higher sodium intake in people of low SES), 3% positive, and 30% neutral. Among diet-based estimates, 41% were negative, 21% positive, and 38% neutral. The random-effects model indicated a 14% relative difference between low- and high-SES groups (95% confidence interval [CI] = –18, –9), corresponding to a global 503 milligrams per day (95% CI = 461, 545) of higher sodium intake among people of low SES. Conclusions. People of low SES consume more sodium than do people of high SES, confirming the current evidence on socioeconomic disparities in diet, which may influence the disproportionate noncommunicable disease burden among disadvantaged socioeconomic groups. Public Health Implications. It is necessary to focus on disadvantaged populations to achieve an equitable reduction in sodium intake to a population mean of 2 grams per day as part of the World Health Organization’s target to achieve a 25% relative reduction in noncommunicable disease mortality by 2025.